Train the research supervisors for continuing professional development - Ismail, Affero; Zainal Abiddin, Norhasni (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Students are now the central of institutions’ structure where the focus should be given based on their demands towards best training services and also supervisors’ professional consideration. This scenario has substantial influence to the image of academic institution. Thus, research supervisor in institutions need to be prepared with extensive professional qualification. It does not only serve for customers’ satisfaction, but also a need in staffs’ continuing professional development. This article will discuss the important skills and responsibilities of a supervisor to practice.